2018
DOI: 10.1073/pnas.1716470115
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of advillin in somatosensory neuron subtype-specific axon regeneration and neuropathic pain

Abstract: SignificanceAn estimated 20 million people in the United States have chronic neuropathic pain, but current analgesics are nonspecific or insufficiently effective. Here we show that advillin, a sensory neuron-specific protein, modulates axonal regeneration of a specific subset of pain-sensing afferent neurons (nociceptors) that binds with isolectin B4 and neuropathic pain. In addition, we identify the cell behavior of advillin shed-off from the growth cone in the context of axonal regeneration and thus detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 61 publications
1
28
0
Order By: Relevance
“…1 f). Dorsal root ganglia harbor sensory neurons that are known to express Avil , but not Vil (Chuang et al 2018 ). In our hand, the anti-villin antibodies did not show cross-reactivity with mouse advillin, because they failed to label dorsal root ganglia neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 f). Dorsal root ganglia harbor sensory neurons that are known to express Avil , but not Vil (Chuang et al 2018 ). In our hand, the anti-villin antibodies did not show cross-reactivity with mouse advillin, because they failed to label dorsal root ganglia neurons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In mice, a comparison of the transcriptional profiles of small intestinal TRPM5-positive tuft cells with that of other enterocytes revealed that villin was expressed equally strong in both cell populations, while advillin expression was restricted to tuft cells (Bezençon et al 2008 ). To be sure that our immunohistochemical tools had an adequate specificity, we stained sections containing taste cells, which express both, villin and advillin, and dorsal root ganglia that are known to express advillin but not villin (Chuang et al 2018 ). We found similar staining patterns for villin and advillin in taste cells, however many dorsal root ganglia neurons stained for advillin, but not for villin, thus ruling out advillin cross-reactivity of the anti-villin antibody.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these signal pathways, some are known to be related to SCI, such as CAMs (Brook et al 2000;Zhang et al 2008), ECM-receptor interaction (Zhou et al 2017 Manuscript to be reviewed pathway (Li et al 2019a;Li et al 2019b;Zhang et al 2017) and focal adhesion (Chuang et al 2018;Graham et al 2016;Hao et al 2018).…”
Section: Discussionmentioning
confidence: 99%